Christian Ethics of Creation - Rosenberger, Michael (Nomos Verlagsgesellschaft mbH & Co. KG, 2022)
If the enormous ecological challenges of the present are to be overcome, clear ethical orientations and deep sources of inner strength are needed. This book reflects the potential of Christian tradition to establish an ethics and spirituality of Creation. To this end, it draws on biblical and liturgical impulses as well as on the encyclical Laudato si by Pope Francis and relates them to scientific, sociological and economic considerations. On this basis, it develops a perspective of action and hope that is sustainable through difficulties and disappointments.